Islamic State Senior High School: The Effect of Using Talking Stick Method on Student’s Speaking Performance (English Community Journal, 2023)
This study discussed about using Talking Stick Method on students’ speaking skill at MAN 3 Kota Jambi. The goals of the research are to find out the effect of Talking Stick Method on Students’ Speaking Performance after being taught by using Talking Stick Method and to find out significant different between students’ who are taught by using Talking Stick Method and those who are not. This research used quasi experimental method with quantitative approach. Sample of the research were 60 students which experimental class was 30 students and control class 30 students. The data collection is used pre-test and post-test. Data analysis is used speaking test. The result of this research shows that applying Talking Stick Method affected on students’ speaking performance. It can be seen at paired sample t- test and independent sample t-test. The result of the average students’ speaking score from the same group who taught by using Talking Stick Method got score 0.000 which can be seen from criteria of hypothesis if the score lower than 0.05 it means Ha is accepted. And the result of independent sample t- test shows that the mean of different was 13. 26667 and the  significant 2-tailed ? 0.05 (0.000 ? 0.05). It can be seen there are difference effect of students’ speaking skill between experimental and control class. To sum up, it can be concluded that there was any difference significant effect of students’ speaking skill between students’ who were taught by using Talking Stick Method and students who were taught by using conventional Method at MAN 3 Kota Jambi.